Ultrasonic melt treatment of light alloys - Barbosa, J. (2019)
The application of ultrasonic vibrations when casting aluminium alloys can improve the final quality of castings. Moreover, ultrasound has no direct environmental impact as compared to traditional melt treatment routes. Ultrasound has been used with different purposes in aluminium casting: (1) degassing of aluminium alloys leading to high density and virtually gas porosity free castings; (2) promoting nucleation, thus leading to highly refined microstructures, including refinement and dispersion of intermetallic compounds; (3) improving castings mechanical properties either by promoting heterogeneous nucleation and development of equiaxed globular structures or dendrite fragmentation. This article presents the experimental work carried out so far at the University of Minho, Portugal, in this field and focuses on the results and benefits of ultrasonic melt processing when compared with traditional alternatives like the chemical routes.